Influence of the Gamma Ray towards Porosity Evaluation of the Rocks Using Well Log Measurement - Puguh Hiskiawan (Jurnal ILMU DASAR, 2014)
Well Log method is one of the geophysics methods used to examine rock structure under earth surface. This research is studied by using utilizing influence of the gamma ray to physical parameter on well log measurement. This research is explained to compare the measuring data with some physical parameters. The results shown that the rock density was about 2.00 – 2.50 g/cc, the rock porosity was round 2.00 – 2.50 g/cc, whereas the resistivity has 2 Ωm to 60 Ωm. All those vaiables were measured at same depth 3420 – 3470 ft. Furthermore, the self potential value was the highest negatively. The result from physical parameter provided meaning about anomaly positively of hydrocarbon existing.Keywords: Well Log, gamma ray, hydrocarbon